2018
DOI: 10.3897/compcytogen.v12i4.31015
|View full text |Cite
|
Sign up to set email alerts
|

Pilot satellitome analysis of the model plant, Physcomitrella patens, revealed a transcribed and high-copy IGS related tandem repeat

Abstract: Satellite DNA (satDNA) constitutes a substantial part of eukaryotic genomes. In the last decade, it has been shown that satDNA is not an inert part of the genome and its function extends beyond the nuclear membrane. However, the number of model plant species suitable for studying the novel horizons of satDNA functionality is low. Here, we explored the satellitome of the model “basal” plant, Physcomitrellapatens (Hedwig, 1801) Bruch & Schimper, 1849 (moss), which has a number of advantages for deep functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
(94 reference statements)
1
26
0
Order By: Relevance
“…rDNA. There are several examples where satDNA originated from the IGS or rDNA coding genes (Garrido-Ramos 2015; Plohl 2012; Kirov et al 2018) for example, the satDNA jumper, in the Phaseolus genus, derives from the NTS of the 5S rDNA (Ribeiro et al 2017), showing that this phenomenon is quite common, even in plants in low proportions of satDNA and TEs increased genomes.…”
Section: Edulismentioning
confidence: 99%
“…rDNA. There are several examples where satDNA originated from the IGS or rDNA coding genes (Garrido-Ramos 2015; Plohl 2012; Kirov et al 2018) for example, the satDNA jumper, in the Phaseolus genus, derives from the NTS of the 5S rDNA (Ribeiro et al 2017), showing that this phenomenon is quite common, even in plants in low proportions of satDNA and TEs increased genomes.…”
Section: Edulismentioning
confidence: 99%
“…This is in line with a comparative whole genomic methylation analysis of M. polymorpha that showed reduced 35S rDNA methylation compared with other repeats (Schmid et al, 2018). In P. patens , a contig carrying several rDNA copies seemed to be almost devoid of DNA methylation (Kirov et al, 2018). The authors suggested that the contig may derive from an active part of the array and that inactive condensed rDNA arrays may have different methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the rDNA chromatin condensation in bryophytes relies on other epigenetic mechanisms, such as noncoding RNAs. In this context, transcripts derived from IGS subrepeats were identified in P. patens (Kirov et al, 2018). In any case, it is likely that silencing and accurate nuclear position of rDNA may function without significant cytosine methylation of units in some bryophyte species at least.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations